The Interplay between Emotion and Cognition in Autism Spectrum Disorder: Implications for Developmental Theory - Gaigg, Sebastian B. (Frontiers in Integrative Neuroscience, 2012)
Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder that is clinically defined by abnormalities in reciprocal social and communicative behaviours and an inflexible adherence to routinised patterns of thought and behaviour. Laboratory studies repeatedly demonstrate that autistic individuals experience difficulties in recognising and understanding the emotional expressions of others and naturalistic observations show that they use such expressions infrequently and inappropriately to regulate social exchanges. Dominant theories attribute this facet of the ASD phenotype to abnormalities in a social brain network that mediates social-motivational and social-cognitive processes such as face processing, mental state understanding and empathy. Such theories imply that only emotion related processes relevant to social cognition are compromised in ASD but accumulating evidence suggests that the disorder may be characterised by more widespread anomalies in the domain of emotions. In this review I summarise the relevant literature and argue that the social-emotional characteristics of ASD may be better understood in terms of a disruption in the domain-general interplay between emotion and cognition. More specifically I will suggest that ASD is the developmental consequence of early-emerging anomalies in how emotional responses to the environment modulate a wide range of cognitive processes including those that are relevant to navigating the social world.